Clinical Analysis of the Curative Effect of a Transnasal Ileus Tube in the Treatment of Small Bowel Obstruction Caused by a Phytobezoar - Yong-Xu Lin; Sun-Jian Wang; Hui-Shun Liang; Su Lin; Li-Yong Bian; Jian Ding; Dan Li (Gastroenterology Research and Practice)
Objective. To investigate the curative effect of a transnasal ileus tube in the treatment of small bowel obstruction caused by a phytobezoar. Methods. Seventy-one patients with small bowel obstruction caused by a phytobezoar who underwent treatment in three provincial tertiary grade A hospitals in Fujian Province from March 2011 to February 2020 were included in this study. Patients were divided into the following two groups according to the treatment received: (1) conservative group, comprising patients who received medical conservative treatment, and (2) combined group, including patients who received combined medical conservative treatment and transnasal ileus tube placement. The clinical symptoms, changes in abdominal imaging, tube depth of the first day, reduction of pressure volume on the first day after catheterization, length of hospital stay, and nonsurgical rate were compared between the combined and conservative groups. Results. There was no significant difference in age, sex, history of previous abdominal surgery and abdominal radiotherapy, symptoms at admission, duration of symptoms before admission, signs at admission, laboratory data, and obstruction position between the combined and conservative groups. There was a statistically significant difference in the nonsurgical rate (19/24 vs. 23/47, P=0.014) between the combined and conservative groups. Logistic analysis showed that the duration of symptoms before admission, albumin level, and use of a transnasal ileus tube might be independent factors affecting the transition to surgery for patients with small bowel obstruction caused by a phytobezoar (P<0.05). Conclusion. Timely conservative medical treatment with transnasal ileus tube placement can effectively improve the nonsurgical rate of small bowel obstruction caused by a phytobezoar. The duration of symptoms before admission, albumin level, and use of a transnasal ileus tube were closely related to whether patients with small bowel obstruction caused by phytobezoar were transferred to surgery.